N 1-methyladenosine methylation in tRNA drives liver tumourigenesis by regulating cholesterol metabolism - Yanying Wang (Nature Portfolio, 2021)
Metabolic adaptation has been reported to promote cancer, yet the underlying mechanisms are not clear. Here, the authors show that m1A methylation in tRNA regulates cholesterol metabolism in liver cancer stem cells and m1A inhibition decreases tumourigenesis in preclinical models of hepatocellular carcinoma.